The Influence of Compensation, Workload and Work Environment on Employees - Yanti, Sri; A, Priyanka Reggina (Zona Manajerial: Program Studi Manajemen (S1), 2022)
The role of human resources is very important to achieve company goals. This of course does not escape from various supporting factors in increasing employee productivity or work performance such as a supportive work environment, workload stability and also providing rewards that are commensurate with employee performance. The purpose of this study is to analyze the effect of compensation, working environment and workload through work satisfaction on Badan Pengusahaan Batam. The method used is multiple linear regression analysis. The study population of 1782 employees and samples used by 100 respondents. Research shows that the Compensation and Working Environment partially significant effect on the Work Satisfaction. While Workload partially not significant effect on the Work Satisfaction. Simultaneously Compensation, Working Environment and Workload have significant effect on the Work Satisfaction.